Hippocampus More than Just Memory - Burman, Douglas D. (IntechOpen, 2023)
Ever since side effects from bilateral hippocampectomy were identified in Henry Molaison (patient "HM") during the 1950s, a critical role of the hippocampus has been recognized in the formation of declarative episodic memories. Other cognitive functions have since been proposed, such as a role in navigation, but memory has often been suggested to explain hippocampal involvement. Proving a distinct functional role in cognition is difficult, as memory can be implicated in most cognitive activities. Even when a behavior relies on memory, however, the functionality of the hippocampus extends far beyond, especially evident during activities requiring interactions between cognitive systems. Relational memory is supported by hippocampal connections with widespread regions of the cortex; these interconnections also play a fundamental role in children's writing abilities and expertise in musical performance. Besides enhancing individual lives, such activities can play a vital role in sustaining cultural values across generations. Interactions with the environment that do not directly depend on mnemonic activity can affect plasticity in hippocampal connections, modified through natural chemicals, pharmacological drugs, and non-pharmacological behaviors. Navigational properties of the hippocampal system are not limited to memory, containing the same navigational elements as our Global Positional System (GPS). Even cognitive deficits arising from hippocampal lesions in "HM" were not limited to memory, as they included deficits in understanding cognitive relationships available in visual scenes, novel sentence contexts, and humorous situations. This book shows an expansive role of the hippocampus in cognition that goes beyond its recognized role in generating new episodic memories.